Urokinase‐type plasminogen activator (uPA) is not essential for epithelial sodium channel (ENaC)‐mediated sodium retention in experimental nephrotic syndrome. (20th May 2019) - Bohnert, Bernhard N.; Daiminger, Sophie; Wörn, Matthias; Sure, Florian; Staudner, Tobias; Ilyaskin, Alexandr V.; Batbouta, Firas; Janessa, Andrea; Schneider, Jonas C.; Essigke, Daniel; Kanse, Sandip; Haerteis, Silke; et al.
Abstract: Aim: In nephrotic syndrome, aberrantly filtered plasminogen (plg) is converted to active plasmin by tubular urokinase‐type plasminogen activator (uPA) and thought to lead to sodium retention by proteolytic activation of the epithelial sodium channel (ENaC). This concept predicts that uPA is an important factor for sodium retention and that inhibition of uPA might be protective in nephrotic syndrome. Methods: Activation of amiloride‐sensitive currents by uPA and plg were studied in Xenopus laevis oocytes expressing murine ENaC. In doxorubicin‐induced nephrotic mice, uPA was inhibited pharmacologically by amiloride and genetically by the use of uPA‐deficient mice ( uPA −/− ). Results: Experiments in Xenopus laevis oocytes expressing murine ENaC confirmed proteolytic ENaC activation by a combination of plg and uPA which stimulated amiloride‐sensitive currents with concomitant cleavage of the ENaC γ‐subunit at the cell surface. Treatment of nephrotic wild‐type mice with amiloride inhibited urinary uPA activity, prevented urinary plasmin formation and sodium retention. In nephrotic mice lacking uPA ( uPA −/− ), urinary plasmin formation from plg was suppressed and urinary uPA activity absent. However, in nephrotic uPA −/− mice, sodium retention was not reduced compared to nephrotic uPA +/+ mice. Amiloride prevented sodium retention in nephrotic uPA −/− mice which confirmed the critical role of ENaC in sodium retention. Conclusion: uPA is responsible for the conversion of aberrantly filtered plasminogen to plasmin in the tubular lumen in vivo. However, uPA‐dependent plasmin generation is not essential for ENaC‐mediated sodium retention in experimental nephrotic syndrome.